Intraday and interday reliability of ultra-short-term heart rate variability in rugby union players - Nakamura, F. Y.; Pereira, L. A.; Esco, M. R.; Flatt, A. A.; Moraes, J. E.; Cal Abad, C. C.; Loturco, I. (The Journal of Strength and Conditioning Research, 2017)
The aim of this study was to examine the intraday and interday reliability of ultra-short-term vagal-related heart rate variability (HRV) in elite rugby union players. Forty players from the Brazilian National Rugby Team volunteered to participate in this study. The natural log of the root mean square of successive RR interval differences (lnRMSSD) assessments were performed on 4 different days. The HRV was assessed twice (intraday reliability) on the first day and once per day on the following 3 days (interday reliability). The RR interval recordings were obtained from 2-minute recordings using a portable heart rate monitor. The relative reliability of intraday and interday lnRMSSD measures was analyzed using the intraclass correlation coefficient (ICC). The typical error of measurement (absolute reliability) of intraday and interday lnRMSSD assessments was analyzed using the coefficient of variation (CV). Both intraday (ICC = 0.96; CV = 3.99%) and interday (ICC = 0.90; CV = 7.65%) measures were highly reliable. The ultra-short-term lnRMSSD is a consistent measure for evaluating elite rugby union players, in both intraday and interday settings. This study provides further validity to using this shortened method in practical field conditions with highly trained team sports athletes.